A Transitivity Analysis of the Character's Actions in Joseph Jacobs's Fairy Tales - Ahmad Faizin; Hafidzatul Azizah; Putu Zahra Amalia Atiyoti Jwalita (Universitas Gadjah Mada, 2022)
This study aims at examining the transitivity processes occurred in the characters’ action in Joseph Jacobs’s Fairy Tales. Language style for children literature has its distinction from other fictions. Such lexical and the dictions selection become its focus primarily at the main figure’s action. The purpose of this study is not only to provide worthwhile information particularly at the language style of literature for children in case of Joseph Jacobs’s fairy tales but also to remedy the neglected focus on the earlier studies which analyzes the mentioned object as well. This study used the methodology of descriptive qualitative research. To analyze the research objective, this study used Halliday’s transitivity theory which examines the processes of a sentence. Based on the data analysis, the results found 56 data in total contained with several processes as follows; 30 material processes, 5 mental processes, 5 behavioural processes, 4 verbalization, 3 relational processes, and an existential processes.